Bahasa Indonesia Bahasa Indonesia - Mawarni Saputri; Qory Oktaria; Alnia Junaidi; M. Agis Ardiansyah (Postgraduate, University of Mataram, 2023)
The aim of this study was to determine the effect of the intensity of the yellow LED light and the sound intensity of religious music (Asmaul Husna) on the growth of various types of chili plants in indoor system. The research method uses experimental research. This research was conducted in Baitussalam District, Aceh Province. This research was conducted for a month. Based on the results and discussion, it can be concluded that exposure to LED lights and religious music (Asmaul Husna) has a fairly good effect on the growth of stem height, number of leaves and leaf width of the three types of chili plants tested. This is because the addition of light in the form of LEDs and sound can help the plant photosynthesis process to be more productive and accelerate the growth of the third type of chili. From the three types of chili, the most significant effect is in terms of plant height, leaf width and number of leaves found in chili peppers compared to the results obtained on cayenne pepper and green chili.